Psychological Trait and Situation Affecting through Inspiration of Public Mind to Energy Conservation Behavior of Undergraduate Student - Pimdee, Paitoon; Thiengkamol, Nongnapas; Thiengkamol, Tanarat (Mediterranean Journal of Social Sciences, 2012)
This research objective was to study psychological trait and situation affected to energy conservation behavior and inspirationof public mind of undergraduate student of KMITL in the first semester of academic year 2012. The sample group of 800 students weresampling with Multi-stage random sampling technique. Questionnaire was used as research tool that was examined for content validityby 5 experts and it was tried out with the group that was not sample group. The reliability in aspects of psychological trait, situation,inspiration of public mind and energy conservation behavior were 0.88, 0.83, 0.93, and 0.85 respectively. Data analysis was conductedby Hierarchical Multiple Regression. The findings showed as followings: 1. The group of psychological trait variables was able to predictthe group of energy conservation behavior variables with 35.2%. The most important predictors were future orientation and self control,and mental health. Moreover, it also predicted the group of inspiration of public mind variables with 35.8%. 2. The group of situationvariables was able to predict the group of energy conservation behavior variables and more than the group of psychological traitvariables with 9.3% (increased from 35.2 to 44.5%) and subgroup more than the group of psychological trait variables by increasingbetween 28.2%-40.6%. The most important predictors were perception of family role model and media perception.